Identification of tetrodotoxin-producing bacteria from goby Yongeichthys criniger. (15th September 2015) - Wei, Fen; Ma, Tinglong; Gong, Xiaoling; Zhang, Na; Bao, Baolong
Abstract: Toxic goby fish ( Yongeichthys criniger ) containing tetrodotoxin (TTX), from Zhanjiang, Guangdong province, China, were screened for TTX-producing bacteria. Two toxic bacterial strains were isolated from the liver of Y. criniger and respectively denoted XC3-3 and XL-1. TTX production by the strains was confirmed by mouse bioassay, enzyme-linked immunosorbent assay and high performance liquid chromatography coupled with mass spectrometry. Based on morphological, physiological and biochemical characteristics and 16S rDNA phylogenetic analysis, strain XC3-3 was identified as Enterobacter cloaca and XL-1 was closely related to Rahnella aquatilis . These findings show for the first time that TTX-producing bacteria are symbiotic bacteria in goby and suggest that bacterial strains are at least partially responsible for TTX accumulation in Y. criniger . Highlights: We present the first report of TTX-producing bacteria isolated from goby species. We provide new evidence for exogenous sources of TTX in goby. We identify the TTX-producing strains Enterobacter cloaca and Rahnella aquatilis . Two genera are added to the list of TTX-producing bacteria.